Beyond Traditional Antimicrobials: A Caenorhabditis elegans Model for Discovery of Novel Anti-infectives - Kong, Cin; Eng, Su-Anne; Lim, Mei-Perng; Nathan, Sheila (Frontiers in Microbiology, 2016)
The spread of antibiotic resistance amongst bacterial pathogens has led to an urgent need for new antimicrobial compounds with novel modes of action that minimize the potential for drug resistance. To date, the development of new antimicrobial drugs is still lagging far behind the rising demand, partly owing to the absence of an effective screening platform. Over the last decade, the nematode Caenorhabditis elegans has been incorporated as a whole animal screening platform for antimicrobials. This development is taking advantage of the vast knowledge on worm physiology and how it interacts with bacterial and fungal pathogens. In addition to allowing for in vivo selection of compounds with promising anti-microbial properties, the whole animal C. elegans screening system has also permitted the discovery of novel compounds targeting infection processes that only manifest during the course of pathogen infection of the host. Another advantage of using C. elegans in the search for new antimicrobials is that the worm itself is a source of potential antimicrobial effectors which constitute part of its immune defense response to thwart infections. This has led to the evaluation of effector molecules, particularly antimicrobial peptides (AMPs), as candidates for further development as therapeutic agents. In this review, we provide an overview on the use of the C. elegans model for identification of novel anti-infectives. We highlight some highly potential lead compounds obtained from C. elegans-based screens, particularly those that target bacterial virulence or host defense to eradicate infections, a mechanism distinct from the action of conventional antibiotics. We also review the prospect of using C. elegans AMPs as an antimicrobial strategy to treat infections.